2019
DOI: 10.3389/fimmu.2019.02145
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: Fine Tuners of Monocyte Heterogeneity

Abstract: Small non-coding microRNAs (miRNAs) have been found to play critical roles in many biological processes by controlling gene expression at the post-transcriptional level. They appear to fine-tune the immune response by targeting key regulatory molecules, and their abnormal expression is associated with immune-mediated inflammatory disorders. Monocytes actively contribute to tissue homeostasis by triggering acute inflammatory reactions as well as the resolution of inflammation and tissue regeneration, in case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Circulating monocytes are a heterogeneous population that are classified into three subsets according to CD14 and CD16 expression (classical CD14 ++ CD16 − , intermediate CD14 ++ CD16 + , and nonclassical CD14 + CD16 ++ ). The subsets have characteristic phenotypic, functional, transcriptomic, and epigenetic profiles [ 40 , 41 ], including subset-specific miRNA expression [ 42 ] and DNA methylation profiles linked to distinct immunological processes [ 43 ]. Several studies have shown an increase in circulating CD16 + subsets in elderly vs. young adult monocytes [ 14 , 15 , 17 ], though others have shown no difference in proportions of subsets between elderly and young adults [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Circulating monocytes are a heterogeneous population that are classified into three subsets according to CD14 and CD16 expression (classical CD14 ++ CD16 − , intermediate CD14 ++ CD16 + , and nonclassical CD14 + CD16 ++ ). The subsets have characteristic phenotypic, functional, transcriptomic, and epigenetic profiles [ 40 , 41 ], including subset-specific miRNA expression [ 42 ] and DNA methylation profiles linked to distinct immunological processes [ 43 ]. Several studies have shown an increase in circulating CD16 + subsets in elderly vs. young adult monocytes [ 14 , 15 , 17 ], though others have shown no difference in proportions of subsets between elderly and young adults [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Targets of differentially expressed miRNAs were mostly related to motility and cell death processes [ 41 ]. miRNA-17, miRNA-18a/b, miRNA-19a/b, miRNA-20b, miR-27a, miRNA-106a, miR-119-5b and miR-345 were overexpressed in classical monocytes, whereas miRNA-132, miRNA-146a, miRNA-342-3p, miR-379, miR-382, miR-411, miR-637 and miR-654-3p were overexpressed in non-classical monocytes [ 50 , 82 ] ( Figure 2 ). Recently, the Ziegler-Heitbrock group presented a lower expression of miR-20a and miR-106b in non-classical monocytes defined by both CD14/CD16 expression and via Slan [ 83 ].…”
Section: Monocytes—diversity and Cancermentioning
confidence: 99%
“… A dot plot representing three subsets of human monocytes according to the expression of CD14 and CD16 supplemented with data concerning upregulated miRNA [ 41 , 49 , 50 ]. …”
Section: Figurementioning
confidence: 99%
“…Richard et al focused on the sequencing of miRNAs among monocyte subsets in humans and mice to identify their role in monocyte heterogeneity. From their work, they suggested three miRNAs-miR-21, miR-150, and miR-146aas immune regulators that mediate resolution of inflammation in the myeloid cells (48). MicroRNA profiling of intermediate monocytes (CD14++ CD16+) yielded a unique miRNA profile, and their connected pathways are involved in gene regulation, TLR, and cytokine-mediated signaling, phagocytosis, antigen processing, and presentation, as well as lipid and triglyceride metabolism (49).…”
Section: Monocyte and Macrophage Mirnasmentioning
confidence: 99%